2019
DOI: 10.1016/j.jaip.2019.02.031
|View full text |Cite
|
Sign up to set email alerts
|

Acute Management, Diagnosis, and Follow-Up of Suspected Perioperative Hypersensitivity Reactions in Flanders 2001-2018

Abstract: Background: Despite numerous efforts to describe the clinical manifestations and the epidemiology of perioperative hypersensitivity (POH), there remains room to increase awareness among anesthetists and immunologists/allergists.Objective: To report the findings of a 17-year survey of suspected POH in Antwerp (Belgium).Methods: We analyzed clinical and diagnostic data from 715 patients referred because of a suspected POH reaction, between January 1, 2001 and May 31, 2018. 456 patients demonstrating a POH could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(28 citation statements)
references
References 110 publications
0
20
0
Order By: Relevance
“…While such reactions are still rare, they are the elicitor in up to 10% of perioperative anaphylaxis in Denmark and Belgium. 5,6 The route of sensitization to CHX, either IgE or T cells specific, is still unclear. CHX represents a bipolar compound with two chloroguanide endings linked by a hexamethylene bridge (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…While such reactions are still rare, they are the elicitor in up to 10% of perioperative anaphylaxis in Denmark and Belgium. 5,6 The route of sensitization to CHX, either IgE or T cells specific, is still unclear. CHX represents a bipolar compound with two chloroguanide endings linked by a hexamethylene bridge (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Exposure to CHX‐containing devices (eg, in central venous catheters, Arrow®) or CHX‐coated urethral gels (eg, Instillagel®, Chlorhexidine Gluconate Solution; Farco‐Pharma GmbH) may even result in anaphylaxis and anaphylactic shock. While such reactions are still rare, they are the elicitor in up to 10% of perioperative anaphylaxis in Denmark and Belgium 5,6 …”
Section: Introductionmentioning
confidence: 99%
“…A recent study of perioperative hypersensitivity showed that high tryptase values were detected more frequently in life‐threatening reactions than in non‐life‐threatening ones. Furthermore, mast cell activation determined using the formula tryptase > 1.2 × baseline‐tryptase + 2 µg/L was more frequent in life‐threatening reactions and in adults compared with children 64,65 …”
Section: In Vitro Testsmentioning
confidence: 96%
“…Furthermore, mast cell activation determined using the formula tryptase > 1.2 × baseline-tryptase + 2 µg/L was more frequent in life-threatening reactions and in adults compared with children. 64,65 Histamine is the most abundant and important inflammatory mediator for acute anaphylaxis, with plasma sensitivity ranging from 61%-92% and specificity from 51%-91%. 62 However, it is difficult to assess due to its short half-life in serum (20 minutes).…”
Section: Inflammatory Mediatorsmentioning
confidence: 99%
“…Hypersensitivity reactions to latex exposure have been reported to occur more frequently in childhood. In the adult population, hypersensitivity reactions were more common in women approximately 40 years of age and in men over 50 years of age [ 9 , 15 , 16 , 18 , 22 , 31 , 38 , 56 ]. An increased risk in mastocytosis, asthma, hypertension, coronary artery disease, obesity and morbid obesity, especially with the use of angiotensin-converting enzyme inhibitors and beta-blockers, was also reported [ 7 , 8 , 55 ].…”
Section: Triggering Factorsmentioning
confidence: 99%